Association of Bacterial Vaginosis with Preterm Delivery (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Objective: To find out the effect of bacterial vaginosis on preterm delivery. Bacterial vaginosis (BV) is one of most the common presentation of women in their reproductive age group. Its prevalence is relatively high in the obstetric population which is mostly responsible for preterm delivery.Methods: This study tried to find out effect of BV on preterm delivery. The study included 100 pregnant women aged 15 to 35 years, between 28-36 weeks of gestation, with abnormal vaginal discharge and clinically suspected BV. Obstetrics outpatient department of BSMMU was selected for the study. The study population was divided into two groups (63 culture negative and 37 culture positive for BV).Results: Mean (±SD) age of BV negative and positive subjects were 24.59+5.18 and 23.89+4.77 years respectively (statistically not significant). Although socioeconomic status, educational status and gravida did not statistically show any significant difference between two groups. Significantly high number of BV positive women delivered prematurely (73%) compared to BV negative (25.4%) (P